Shaping and enhancing airport lounge experiences: the application of brand personality and image congruity theories - Lee, Sanghyeop; Chua, Bee-Lia; Kim, Hyeon-Cheol; Han, Heesup (Emerald, 2017)
Purpose: In consideration of the lack of research regarding airline lounge customers’ behavior, the purpose of this study was to examine the relationships among brand personality, self-congruity, functional congruity, positive emotion, customer satisfaction and revisit intentions in airline lounges. Design/methodology/approach: On the basis of theoretical associations among study constructs, a conceptual model was proposed and tested using the data collected from airline lounge patrons through an online survey. Findings: The empirical results showed that brand personality was positively related to self-congruity. Self-congruity was significantly associated with positive emotions and functional congruity. In addition, functional congruity was significantly associated with positive emotions. This result also indicated that positive emotion significantly influenced customer satisfaction. The mediation tests showed that both self-congruity and functional congruity significantly affected customer satisfaction through positive emotion. Customer satisfaction was a significant predictor of revisit intentions within the context of airline lounges. Practical implications: Overall, these results help airline lounge operators understand lounge travelers who become more demanding with regard to brand personality, self-congruity and functional congruity. Originality/value: This research was the first to test the effectiveness of image congruity theory in the domain of airline lounges. Our findings contribute to the body of knowledge on customer behaviors in airline lounges and image congruity.